New Constructions of Landsberg Non-Berwaldian (α, β)-Metrics - Elgendi, Salah Gomaa (Contemporary Mathematics, 2025)
In this paper, we present new constructions of non-regular Finsler metrics of (α, β)-type that satisfy the Landsberg condition without being Berwaldian. These examples contribute to the ongoing investigation of the Landsberg-Berwald problem by expanding the class of known non-Berwaldian Landsberg spaces. The results offer deeper insight into the geometric structure and richness of such metrics within the framework of Finsler geometry.